PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS - Purwanti, Sri; Putra, Purniadi; Sunantri , Sri (ILJ: Islamic Learning Journal, 2024)
This research departs from the phenomenon of habituation carried out by students of SDN 03 Makong when Islamic Religious Education learning begins, students will read Iqro' for grades 1-3 while for grades 4-6 students will read Jus 'Amma and at dzuhur prayer time a congregational prayer is held for students in grades 4-6 which is usually often done at madrasah schools or boarding schools. The focus of this research is the implications of learning Islamic Religious Education as an effort to form the religious character of students of SD Negeri 03 Makong, Tempunak District, Sintang Regency. This research uses a qualitative approach and uses descriptive analysis methods. Data collection techniques through observation. Interviews and complete documentation. Data analysis using interactive analysis method. Data checking techniques through triangulation, reference materials and member chek. The results of the study can be concluded, among others: the character of students of SD Negeri 03 Makong can be said to be good, this is evidenced by the few students who commit offences at school, but still within reasonable limits. Their behaviour and pattern can be said to be very good. The implication of Islamic Religious Education learning in shaping the religious character of students of SD Negeri 03 Makong is using the exemplary method that is exemplified by the teacher so that it can be imitated by students, such as praying alone without coercion and reading the Koran with the teacher to be more diligent. Having an attitude of tolerance towards others and discipline to be present on time at school.